(untitled) (Research, Society and Development, 2022)
Although dentoalveolar trauma is directly involved with oral health, it also has consequences for the patient’s general health, since its involvement is directly related to functional, aesthetic and social damage. Although there is a great importance of sports activities in child development, its practice is accompanied by an increase in the number of dentoalveolar injuries. The aim of this study was to evaluate the efficacy of the use of mouthguards to prevent potential oral health problems in school-age children. An integrative literature review was carried out to answer the following question: ’’What is the impact of the use of mouthguards on the quality of life related to oral health in school-age children? After applying the inclusion and exclusion criteria, 9 articles were selected for characterization. The use of mouthguards showed to be an effective strategy in reducing traumas generated during the practice of sports activities. Based on the studies presented, the relationship of dentoalveolar traumas with a worsening in quality of life is evident. Sports-related injuries have been observed with high prevalence in children. Based on this assumption, the use of mouthguards has been shown to have a positive impact on the quality of life of children. More studies are needed to have the inference of practical applications of mouthguards, including as a collective health measure, through public policies and strengthening of the content in the periods of training in Dentistry.